Encuentro mundial de los movimientos populares en el Vaticano (27 al 29–X–2014): La fuerza de los excluidos - Czérny, Michael; Foglizzo, Paolo; Cordova, Barbara; E. López, David (Revista de Fomento Social, 2014)
.